RHINOLITH:AN INCIDENTAL RADIOGRAPHIC FINDING (CLINICAL CASE) - Сторожчук, Юлія; Вальчишин, Станіслав; Бурмаков, Михайло; Чочія, Мірза (SWorldJournal, 2025)
The article presents a retrospective analysis of the literature and a detailed description of a clinical case of a patient with asymptomatic rhinolith, discovered incidentally during computed tomography. The analysis also includes generalized statistics